Patterns Of Torus Mandibularis And Torus Palatinus Among Dental Patients Of A Public Hospital In Karachi - Ramsha Azhar; Salik Rasool; Bushra Jabeen; Umer Hasan; Hasan Baber; Bilal Hussain; Mansoor Akhtar (Journal of Bahria University Medical and Dental College)
Objective: To evaluate the patterns of Torus mandibularis (TM) and Torus palatinus (TP) among the patients attending the dental department of a teaching hospital in Karachi focusing on the age and gender. Study Design and Setting: A cross-sectional study conducted at dental OPD of Dow International Dental College/Hospital DUHS, conducted from November 2017 to October 2018. Methodology: The calculated sample size of the study was 278. Written consent was taken from each participant prior to starting investigation. The questionnaire comprises of 17 variables, evaluating demographics, state of dentition and characteristics of presence of any suspected tori. Participants were examined via sterilized mouth mirror and probe. Impressions were then taken from the participants having positive findings to further evaluate the size and shape to tori. Results: The prevalence of (TM) and (TP) were found to be 3.3% and 0.6% respectively. (TM) was predominantly found in males and (TP) was more frequent in females. Both (TM) and (TP) were most prevalent during fifth decade of life irrespective of gender. Bilateral unilobulated (TM) in the premolar region of the mandible were found to be most recurrent. Lobulated (TP) of large size was found to be prevalent in this study. Conclusion: Study has shown very less prevalence of tori in population of Karachi, Pakistan. The prevalent patterns of tori were found to be bilateral unilobulated in the premolar region of the mandible and large, lobular in the palate. The relationship of tori with age and gender was not significant.